Promotor Hypomethylation Mediated Upregulation of VCAN Targets Twist1 to Promote EndMT in Hypoxia‐Induced Pulmonary Hypertension - Jinyan Yu; Shanchao Hong; Lingjia Yang; Shugao Ye; Zhen Yu; Zheming Zhang; Ziteng Wang; Shulun Huang; Yuan Chen; Tao Bian; Yan Wu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Hypoxia‐induced pulmonary hypertension (HPH) is a severe vascular disorder that is characterized by the involvement of endothelial‐to‐mesenchymal transition (EndMT) in its pathogenesis. Our previous research has suggested that the gene versican may have a crucial role in the development of HPH. However, the exact function of versican in HPH requires further investigation. Methods and Results The expression of versican and markers of EndMT was assessed using Western blot, immunohistochemistry, and immunofluorescence. Vascular remodeling and right ventricular hypertrophy in patients with HPH and mice were evaluated through hematoxylin and eosin staining, Masson's staining, and hemodynamic measurements. Protein interactions were validated using co‐immunoprecipitation, and the DNA methylation level of versican was examined using methylation‐specific polymerase chain reaction. Compared with the control, EndMT was observed in patients with HPH, HPH mouse models, and hypoxia‐treated human pulmonary artery endothelial cells, accompanied by a significant increase of versican. Endothelium‐specific knockdown of versican reversed HPH progression and effectively prevented EndMT in mouse models and human pulmonary artery endothelial cells. We further confirmed that versican participated in EndMT by targeting the key transcription factor Twist1. Additionally, the upregulation of versican may be attributed to promoter hypomethylation, which was mediated by reduced DNA methyltransferases activity under hypoxic conditions. Conclusions This study provides the initial evidence showcasing the role of promoter hypomethylation‐mediated versican upregulation in promoting EndMT by targeting Twist1, which facilitates vascular remodeling and the progression of HPH. These findings offer a promising new target for the treatment of HPH.